EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN BERDIFERENSIASI DALAM PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS V SDN 007 LONG MESANGAT - Nurngaini; Siti Maisaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve descriptive writing skills through a differentiated learning model for 5th-grade students at SDN 007 Long Mesangat. The type of research used is classroom action research. The research subjects were fifth-grade students at SDN 007 Long Mesangat in the 2024/2025 academic year, consisting of 25 students, including 13 male students and 12 female students. The factors studied were student factors and learning outcomes in descriptive text writing through a differentiated learning model. Data collection methods included observation, testing, and documentation. Class Action Research was carried out in two cycles, namely cycle I and cycle II, which consisted of three meetings. The conclusion from the research results and discussion was that the differentiated learning model could increase the activities of teachers and students and improve learning outcomes in writing descriptive texts. This was evidenced by the achievement of students' descriptive text writing results in Cycle I Meeting I, which was 57%, Cycle I Meeting II, which was 67%, Cycle I Meeting III, which was 70%, Cycle II Meeting I, which was 73%, Cycle II Meeting II, which was 80%, and Cycle II Meeting III, which was 90%. The conclusion of this study shows that through a differentiated learning model, the learning outcomes of fifth-grade students at SDN 007 Long Mesangat in writing